KELIMPAHAN PLANKTON DI EKOSISTEM PERAIRAN TELUK GILIMANUK, TAMAN NASIONAL, BALI BARAT - Thoha, Hikmah (Makara Journal of Science, 2007)
Plankton abundance in Gilimanuk Bay of National Park Ecosystem, West Bali. An observation of plankton condition in Gilimanuk Bay of National Park, West Bali was conducted during March 2006. This study aimed to observ the environmental quality of Gilimanuk Bay water. The parameters observed were focused on the phytoplankton and zooplankton communities. Ten points of observation was done. Plankton abundance varied with location group from 4428 to 1716224 sel/m3 and 23938 individu/m3 (67.73 %) for microplankton and macroplankton, respectively. Microplankton community structure was dominated by the group of diatoms, such as Coscinodiscus, Chaetoceros, Guinardia, Navicula. Pseudonitzshia. The genus Ceratium (the group of dinoflagellates) was found in relatively abundant, but still normal condition. The structure of macroplankton was dominated by copepods 23938 individu/m3 (67.73 %). The other hand, information about mangrove, sea grass and coral reef and asssosiation with fauna in these ecosystem of Gilimanuk Bay very rarely. We need observed this subject for base line data to improving management of marine resources development.